Developing of PowerPoint Based on Visual Basic for Application as a Interactive Learning Media to Increase Learning Interest - Raisal, Abu Yazid; Hidayat, Muhammad; Jf, Nurul Zahriani (Universitas Muhammadiyah Makassar, 2025)
Student interest in astronomy has often been reported as relatively low due to the abstract nature of its concepts, reliance on mathematical reasoning, and the dominance of English-language resources, which collectively reduce motivation and engagement. This condition underlines the urgency of developing innovative learning media that not only deliver content but also actively stimulate curiosity and participation. The present study aimed to develop and validate interactive learning media for the fundamental astronomy course at Universitas Muhammadiyah Sumatera Utara by utilizing Microsoft PowerPoint integrated with Visual Basic for Applications (VBA). Employing a Research and Development approach based on the ADDIE model, the research was limited to the analysis, design, and development stages, followed by expert validation. The developed media incorporated hyperlink navigation, animations, three-dimensional models, and randomized quizzes with automated scoring and feedback. Validation results indicated that the product achieved an average score of 90.3% from media experts and 96.8% from material experts, both categorized as very valid according to established criteria. These findings confirm the reliability of the product in terms of technical quality, interactivity, and content accuracy. The novelty of this study lies in repurposing a widely available platform into an advanced instructional tool by embedding VBA programming, thereby expanding the pedagogical possibilities of conventional presentation software. In conclusion, the VBA-based PowerPoint media was proven to be highly valid and holds strong potential to enhance students’ learning interest in astronomy. This research contributes to the field of physics education by providing a validated framework for developing interactive, discipline-specific digital learning resources.